2016
DOI: 10.1021/jacs.5b11012
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer and Structure-Specific Fluorescence in Hydrogen Bond-Rich Protein Structures

Abstract: Protein structures which form fibrils have recently been shown to absorb light at energies in the near UV range and to exhibit a structure-specific fluorescence in the visible range even in the absence of aromatic amino acids. However, the molecular origin of this phenomenon has so far remained elusive. Here, we combine ab initio molecular dynamics simulations and fluorescence spectroscopy to demonstrate that these intrinsically fluorescent protein fibrils are permissive to proton transfer across hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
282
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(322 citation statements)
references
References 59 publications
28
282
3
2
Order By: Relevance
“…The emission of dbAF from amyloid fibrils and protein aggregates has been associated with the formation of intermolecular hydrogen bonds as source of electron delocalization. [7, 9, 19] The presence of dbAF from monomeric proteins and their intramolecular hydrogen bonds would be consistent with this interpretation. However, we wanted to explore how far below the structure of folded proteins one could go while preserving dbAF emission.…”
Section: Resultssupporting
confidence: 60%
“…The emission of dbAF from amyloid fibrils and protein aggregates has been associated with the formation of intermolecular hydrogen bonds as source of electron delocalization. [7, 9, 19] The presence of dbAF from monomeric proteins and their intramolecular hydrogen bonds would be consistent with this interpretation. However, we wanted to explore how far below the structure of folded proteins one could go while preserving dbAF emission.…”
Section: Resultssupporting
confidence: 60%
“…7−12 A structural characterization of amyloid clusters is thus an important topic of research in the field. Various approaches have been employed to reveal the morphology of individual amyloid fibrils or clusters directly, for instance, electron microscopy (EM), 2,5,8,12,13 atomic-force microscopy (AFM), 11,12,14−16 and super-resolution fluorescence microscopy. 17−22 However, such methods are slow to perform and can require elaborate sample preparation protocols, making them impractical to perform for screening applications or the analysis of large data sets.…”
mentioning
confidence: 99%
“…Recently, protein fibrils have been found to absorb light in the near-UV range and to emit a structure-specific intrinsic fluorescence in the visible range even in the absence of aromatic amino acids. Most strikingly, this intrinsic visible fluorescence has been characterized to originate from the hydrogen-bonding network of protein fibrils with cross-β structures (Chan et al 2013;Lim et al 2016a;Lu et al 2016;Pinotsi et al 2016). Based on previous studies by us and other groups, a diagnostic probe of this novel intrinsic visible fluorescence can be established which is able to distinguish two different types of the fibril structures.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 96%
“…On the other hand, under some conditions, like the yeast prion proteins (Shorter and Lindquist 2005;Michelitsch and Weissman 2000;Chien and Weissman 2001), the TDP-43 and FUS prion-like domains have been biophysically characterized to form fibril/hydrogel structures with cross-β structures (Han et al 2012;Lim et al 2016a;Lu et al 2016;Kato and McKnight 2017;Murray et al 2017). Very unexpectedly, we discovered that the self-assembly of both TDP-43 and FUS prion-like domains into the fibril structures is highly pHdependent (Lim et al 2016a;Lu et al 2016): at low pH such as 4.0, they remained mostly monomeric for many weeks, while at neutral pH they showed a strong capacity to selfassemble into fibrils with cross-β structures as reflected by the development of intrinsic visible fluorescence, which is a novel protein fluorescence originating from the hydrogenbonding network in β-rich secondary structures (Shukla et al 2004;Chan et al 2013;Lim et al 2016a;Lu et al 2016;Pinotsi et al 2016). Furthermore, as indicated by low NMR temperature coefficients of most backbone amides, we found that, despite being intrinsically disordered, the TDP-43 prion-like domain contains a large number of intra-molecular hydrogen bonds between side chains of Ser, Thr, Asn, Gln and backbone atoms (I of Fig.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 99%
See 1 more Smart Citation